Digital outdoor spaces to improve older people wellbeing: narratives in virtual reality​ - Figueiredo, M.; Eloy, S.; Marques, S. (Zip Scene Conference, 2022)
Societies are globally growing older and living longer. UN foresees by 2050, 16% of the population will be over age 65, contrasting to 9% in 2019, primarily living in big cities. Declining health and other related issues, such as mobility and mental impairments, discourage elders from using public outdoor spaces. The design of more inclusive outdoor spaces is mandatory, and older people perceptions of those environments need to be further studied. Unfortunately, there is a lack of studies considering the emotions and behaviors of older adults regarding the use of outdoor spaces. Research technics such as post-occupancy evaluation, while valid, come late. To improve these areas and better understand the needs of older adults, we pursue to create an interactive digital narrative, where the older person will be able to navigate a virtual environment and convey their emotions and feelings orally or by the use of sensors such as heart rate, skin conductance or eye tracking. The narrative creation is proposed based on previous extensive research about older people perceptions of outdoor public spaces to explore the potential and limitations of virtual reality. In this experience, we argue about the relevance of using interactive storytelling in architecture as a narrative for user experience studies. Placemaking through storytelling is used frequently in interiors, i.e: worship places and museums. We also understand that a user-centered design in architecture improves older people sense of belonging and social cohesion when experiencing outdoor spaces. Using storytelling, we present a storyboard representing the experimental conditions used in user studies conducted in simulated environments with virtual reality. The results from this research are two-fold. On one side, we reflect on architectural storytelling as a resource to engage older users through a placemaking design proposal. On the other side, this research presents modes to develop a user-centered approach that includes older people in the design of public outdoor spaces by collecting their perceptions and behaviors like fear of falling and walkability. With such an approach, designers and decision-makers can assess the suitability of design solutions before their construction and therefore adapt the built environment to the user’s needs.